THE USE OF RELAY ON MESSAGE GAME FOR TEACHINGLISTENING COMPREHENSION ON DESCRIPTIVE TEXTS - Oktavianti, Siti; Sudarsono, Sudarsono; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was aimed to find out whether Relay on Message Game could affectstudents’ listening comprehension of descriptive texts or not and how the effect of Relayon Message Game to the students’ listening comprehension of descriptive texts is.This research was a pre-experimental research consisting of 2 treatments.The test was applied twice at the beginning (pre-test) and at the end (post-test).The treatments were given two times.The sample of this research was 35 students of class VII I selected by using cluster random sampling.The tests were analyzed by using SPSS and effect size formula.The result of this research was analyzed by t-test.The result of t-test shows that t-ratio 8.56 is higher than t-critical 2.032 on table distribution with α = 0.05. The research findings show that teaching using Relay on Message Game affected the students’ listening comprehension of descriptive texts significantly.It is recommended to use Relay on Message Game to teach listening comprehension especially on descriptive texts.Key Words:Relay on Message, Games, Listening comprehension